Acute respiratory failure revealing a multilocular thymic cyst in an infant: a case report - Asma, Bouziri (BioMed Central, 2009)
INTRODUCTION: Multilocular thymic cysts are rare benign lesions of the neck and mediastinum that can occur at any age. In children, multilocular thymic cysts are usually symptomatic after the age of 2 years and produce few symptoms. We present an unusual case of a multilocular thymic cyst diagnosed in a 3-month-old girl and causing severe respiratory failure. CASE PRESENTATION: A 3 month-old-girl, with a medical history of dyspnea and wheezing since the age of 20 days, presented in our pediatric intensive care unit for acute respiratory failure requiring mechanical ventilation. The chest radiograph showed thoracic distension without any other abnormalities. The diagnosis of severe asthma was initially suspected and the patient was treated by intravenous corticosteroids and continuous perfusion of salbutamol without any improvement. A chest tomography scan was performed and demonstrated an anterior mediastinal multiseptated cystic mass extending from the inferior face of the thyroid gland to the left cardiophrenic angle. Sternotomy and excision biopsy were planned urgently. The cystic mass was excised completely. The histopathological examination confirmed the diagnosis of a multilocular thymic cyst. CONCLUSION: The particularities of our observation are the occurrence of a multilocular thymic cyst in a young infant and its presentation by a severe acute respiratory failure mimicking asthma.